Cost effective cooling of photovoltaic modules to improve efficiency. (September 2019) - Sajjad, Uzair; Amer, Mohammed; Ali, Hafiz Muhammad; Dahiya, Anurag; Abbas, Naseem
Abstract: This study presents the performance of solar photovoltaic modules provided with cooling in terms of its normalized power output, performance ratio, and module efficiency. The aim of the study is to improve the performance, efficiency, and development of an economical cooling system by installing photovoltaic modules on the duct of cooled air of air-conditioners being used in most of the houses, offices and other buildings. The performance was researched and compared for two photovoltaic modules, one being cooled and other without cooling. The module being cooled showed 7.2% and 6% higher electrical efficiency and performance ratio respectively compared to the module without cooling. The results obtained in this study comprehend the importance and feasibility of the research. Highlights: An economical PV module cooling method is presented. Two PV modules are experimentally tested and compared. Different performance parameters are calculated and analyzed. PV module provided with cooling showed 7.2% higher electrical efficiency. Short review of similar studies is also presented for the comparison.